Pengaruh Digital Leadership dan Digital Capabilities Terhadap Employee Performance yang Dimediasi oleh Job Satisfaction pada PT Bank Central Asia Tbk Kanwil VIII - Bethabara, Marisela; Fatimah, Asti; Emilisa, Netania (Peneliti.net, 2024)
Employees are an important element and asset in an organization or company. The existence of Employee Performance in a company can certainly have a positive impact on the company's progress and success. This research was conducted on employees of PT Bank Central Asia Tbk Kanwil VIII who have the potential to have high Employee Performance due to having career clarity within the company. This research aims to analyze Digital Leadership, Digital Capabilities, Job Satisfaction and Employee Performance at PT Bank Central Asia Tbk Kanwil VIII. The sample used in this research consisted of 124 employees at PT Bank Central Asia Tbk Kanwil VIII. Testing was carried out using the Structural Equation Model (SEM) in AMOS software, with data collection procedures in the form of questionnaires and literature reviews. The results of this research show that employees feel a lack of Digital Leadership in their work and therefore feel that Employee Performance in the company is still lacking. There is a significant positive influence between Digital Leadership on Job Satisfaction. There is also a significant negative influence between Digital Leadership on employee performance. Therefore, companies need to provide clear digital knowledge to their employees to improve employee performance.